2014
DOI: 10.1037/h0100581
|View full text |Cite
|
Sign up to set email alerts
|

Furthering a behavior analytic account of self-control using relational frame theory.

Abstract: The understanding of self-control from a behavior analytic perspective has developed over the past several decades. Researchers have refined the concept of self-control and developed empirical interventions to support the utilization of self-control training in translational and applied settings. This paper describes self-control training, how interventions have been implemented, and suggestions for future research. Future directions include implementing self-control training procedures from a Relational Frame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…RFT is also proving to have utility in explaining and influencing clinically relevant behavior related to implicit cognitive biases [44], self-control [45], self-compassion [46], mindfulness [47], metaphor [20], experiential avoidance [19], and empathic perspective taking [48,49 ]. Indeed, though awaiting validation from randomized control trials, RFT is in the early stages of being directly applied as Relational Frame Therapy [50,51].…”
Section: Solutions From Relational Frame Theorymentioning
confidence: 99%
“…RFT is also proving to have utility in explaining and influencing clinically relevant behavior related to implicit cognitive biases [44], self-control [45], self-compassion [46], mindfulness [47], metaphor [20], experiential avoidance [19], and empathic perspective taking [48,49 ]. Indeed, though awaiting validation from randomized control trials, RFT is in the early stages of being directly applied as Relational Frame Therapy [50,51].…”
Section: Solutions From Relational Frame Theorymentioning
confidence: 99%
“…As McKeel and Dixon (2014) remarked, while several studies have shown the utilization of a standard self-control training procedure and variations of it by directly training people to opt for a delayed choice, there is evidence about the role of verbal mediation in teaching individuals to choose larger and more delayed reinforcers over smaller and immediate ones (e.g., Binder, Dixon, & Ghezzi, 2000;Dixon & Holton, 2009). We submit that an RFT perspective could be useful to explain how language may play an important role for manipulating responses in tasks that involve choices with delayed outcomes.…”
Section: Delay Discounting and Choice Behaviormentioning
confidence: 99%
“…From there, researchers could examine ACT in combination with various traditional behavior analytic interventions, for example, examining ACT in combinations with a self-management token system or ACT in combination with the use of signaled multiple schedules. Recent research has proposed the use of self-control training methods and ACT, an example of the potential for combining behavior analytic interventions (i.e., self-control training) and ACT (McKeel and Dixon 2014). Another area for potential research could include examining implementation of ACT, for example, ways in which practitioners can systematically adapt and modify ACT protocols and procedures for use with individuals with disabilities.…”
Section: Summary and Call For Researchmentioning
confidence: 99%